Методи і засоби вимірювання малих тисків - Дебрянська, Р. (Видавництво Національного університету “Львівська політехніка”, 2004)
The basic methods and modern means of low pressure measurement are analysed and the possibility of a laser mode of deriving of an information about low pressure is considered with the purpose of accuracy enhancement of a measurement.
Keywords: 531.787